2007
DOI: 10.1161/strokeaha.106.480111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum S100B Levels Indicate a Higher Risk of Hemorrhagic Transformation After Thrombolytic Therapy in Acute Stroke

Abstract: Background and Purpose-Intracerebral hemorrhage constitutes an often fatal sequela of thrombolytic therapy in patients with ischemic stroke. Early blood-brain barrier disruption may play an important role, and the astroglial protein S100B is known to indicate blood-brain barrier dysfunction. We investigated whether elevated pretreatment serum S100B levels predict hemorrhagic transformation (HT) in thrombolyzed patients with stroke. Methods-We retrospectively included 275 patients with ischemic stroke (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 38 publications
(25 reference statements)
1
82
1
2
Order By: Relevance
“…This process evolves over several days and even weeks post-stroke. In keeping with this concept, Foerch and coworkers reported that serum 100B levels assessed within the early stages of stroke onset did not reflect infarct size [20]. This finding is also supported by several reports that S100B levels only correlate with final infarct volume if determined [24 h after symptom onset [6,7,21].…”
Section: Discussionmentioning
confidence: 68%
“…This process evolves over several days and even weeks post-stroke. In keeping with this concept, Foerch and coworkers reported that serum 100B levels assessed within the early stages of stroke onset did not reflect infarct size [20]. This finding is also supported by several reports that S100B levels only correlate with final infarct volume if determined [24 h after symptom onset [6,7,21].…”
Section: Discussionmentioning
confidence: 68%
“…While several markers, such as NT-BNP, 5,20,21 CRP, [21][22][23][24] D-Dimers, 20,25,26 Interleukin-6, 21,24,27 von Willebrand factor, 28, 29 S-100β, 30 and neuron specific enolase (NSE), 31 have been associated with functional outcome or mortality, only a few biomarkers added to prognosis based on clinical assessment. None of these markers, however, were fully evaluated including assessment of accuracy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Patients at increased risk for HT might have their tPA therapy modified or be administered a drug to prevent HT. Blood biomarkers that have been associated with HT in ischemic stroke include MMP-9, 60,61,122 cellular fibronectin, 62 fibrinogen, 180 S100B, 181 ferritin, 182 activated protein C, 183 thrombin activatable fibrinolysis inhibitor and plasminogen activator inhibitor-1 184 (Table 1). Other molecules that predict HT include: Vascular Adhesion Protein-1, 185 a cell surface and circulating enzyme involved in recruitment of lymphocytes and neutrophils; serum levels of TJPs (CLDN5, OCLN, and CLDN5/ZO1 ratio); 75 and PDGF-CC isoforms, 37 which is activated by tPA and acts on astrocyte PDGFRa (Figure 2).…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%